Black Phosphorous and Cytop Nanofilm-Based Long-Range SPR Sensor with Enhanced Quality Factor. (6th February 2023) - Karki, Bhishma; Uniyal, Arun; Srivastava, Gaurav; Pal, Amrindra
Abstract : This numerical work proposes two novel designs of long-range surface plasmon resonance sensors (LRSPR) using two different coupling prisms. The performance analysis of the proposed sensor has been investigated using the performance parameters like quality factor (Q ), detection accuracy (DA), sensitivity (S ), and full-width half maximum (FWHM). The transfer matrix method (TMM) has been employed to compute reflectance. The role of the basic recognition element (BRE) has been played by the popular two-dimensional (2D) material, black phosphorus (BP), due to its many optoelectrical features. The maximum obtained values for Q, DA, and S are 3333.25 1 / RIU, 250 degree − 1, and 13.33333 degree/RIU for 2S2G coupled sensor design and 3055.5  1 / RIU, 83.33 degree − 1, and 36.66667 degree/RIU for BK7 coupled sensor design. The operating wavelength of 633 nm, followed by the principle of attenuated total reflection (ATR), has been employed to carry out the theoretical investigation.